1987
DOI: 10.1128/mcb.7.3.1078
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of RAD54- and RAD52-lacZ gene fusions in Saccharomyces cerevisiae in response to DNA damage.

Abstract: The RAD52 and RAD54 genes in the yeast Saccharomyces cerevisiae are involved in both DNA repair and DNA recombination. RAD54 has recently been shown to be inducible by X-rays, while RAD52 is not. To further investigate the regulation of these genes, we constructed gene fusions using 5' regions upstream of the RAD52 and RAD54 genes and a 3'-terminal fragment of the Escherichia coli I-galactosidase gene. Yeast transformants with either an integrated or an autonomously replicating plasmid containing these fusions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(74 citation statements)
references
References 41 publications
3
70
1
Order By: Relevance
“…However, the expression of a RAD54-lacZ fusion is reported to be twofold higher in MATa/␣ diploids than MATa/a diploids (9). Therefore, we tested a high-copy-number plasmid expressing RAD54 for suppression of the ␥-ray sensitivity of the rad51-K191R strain.…”
Section: Resultsmentioning
confidence: 99%
“…However, the expression of a RAD54-lacZ fusion is reported to be twofold higher in MATa/␣ diploids than MATa/a diploids (9). Therefore, we tested a high-copy-number plasmid expressing RAD54 for suppression of the ␥-ray sensitivity of the rad51-K191R strain.…”
Section: Resultsmentioning
confidence: 99%
“…The graph represents the relative amount of RADJ6 mRNA in cells released from a factor immediately after UV irradiation (Li), in cells released from a factor 2 h after UV irradiation (0) or in cells maintained in the continuously presence of a factor (@). (5,19,20,23,25). We have shown that repair of the transcriptional silenced HMLa locus is absent in both radl6 and rad7 mutants (36).…”
Section: Discussionmentioning
confidence: 92%
“…In the yeast Saccharomyces cerevisiae >30 genes called RAD genes are known to be involved in DNA repair (1 1,12). Amongst the RAD genes the RAD2, RAD6, RAD7, RAD18, RAD23 and RAD54 genes have been reported to be inducible upon DNA damage and during meiosis (4,5,19,20,(23)(24)(25)(26). The RAD2, RAD7, RAD23 gene products are involved in nucleotide excision repair, RAD6 and RAD18 are required for induced mutagenesis and post-replication repair and RAD54 functions in the repair of double-strand breaks and recombination (12).…”
Section: Introductionmentioning
confidence: 99%
“…This defect prevents rad54D cells from growing on media containing MMS, a mutagen that damages DNA (Chlebowicz and Jachymczyk 1979). The rad54D mutants are also more sensitive to UV radiation than wild-type cells, because of the involvement of Rad54 in the repair of some UVdamaged DNA molecules (Cole et al 1987;KeszenmanPereyra 1990).…”
Section: Resultsmentioning
confidence: 99%